1993
DOI: 10.1046/j.1523-1739.1993.07030510.x
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of an Endangered Plant. I. Creating a New Population of Amsinckia grandiflora

Abstract: The recovery of endangered plants often requires the creation of new populations in order to decrease the risk of extinction. Despite numerous attempts, no plant species have been fully recovered by creating new populations. Here we report on initial efforts to recover Amsinckia grandiflora Kleeb. ex Gray (Boraginaceae) by re‐establishing the species in appropriate habitat within its historic range, with consideration given to genetic and demographic characteristics of the founding population. An experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 22 publications
0
60
0
Order By: Relevance
“…For example, Levin and Clay (71) demonstrated that Phlox drummondii can successfully grow and reproduce at the species margin. Other authors have emphasized the importance of appropriate management practices that insure the viability of newly created populations of Amsinckia grandiflora (72), Erysimum capitatum, and Oenothera deltoides (73). Finally, Primack and Miao (74) concluded from their experimental study on four annual plant species that both site suitability and dispersal ability were limiting local distribution.…”
Section: Seed Dispersal Studymentioning
confidence: 99%
“…For example, Levin and Clay (71) demonstrated that Phlox drummondii can successfully grow and reproduce at the species margin. Other authors have emphasized the importance of appropriate management practices that insure the viability of newly created populations of Amsinckia grandiflora (72), Erysimum capitatum, and Oenothera deltoides (73). Finally, Primack and Miao (74) concluded from their experimental study on four annual plant species that both site suitability and dispersal ability were limiting local distribution.…”
Section: Seed Dispersal Studymentioning
confidence: 99%
“…However, declining populations, especially due to climate change, may eventually necessitate unconventional, directed efforts such as commercial propagation (Winter & Botha 1994;Affolter 1997) and assisted colonization of propagated plants (Vitt et al 2010) in coordination with other means to perpetuate species (Kostyack et al 2011;Maschinski et al 2011;Goodman et al 2012). If listed species need to be propagated to be reintroduced or moved to mitigate for climate change, examples of previous introductions highlight the need for collaborative, monitored studies coordinated by government agencies such as the FWS that (1) consider genetic diversity, (2) take an experimental approach to address ecological questions, such as using common garden experiments in multiple locations, and (3) minimize potential adverse impacts by conducting risk assessment and screening plants for pests and pathogens (Pavlik et al 1993;Gordon 1994;Reinartz 1995;Falk et al 1996;Gordon 1996;Pavlik 1997;Guerrant & Kaye 2007;Wendelberger et al 2008;Weeks et al 2011;. Some major impediments to cooperation include laws that do not require consultation with scientists and agencies for citizen-initiated projects (McDonald 1996), and the fact that long-term commitment is required, especially when efforts begin at a grassroots level (Falk et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of the recommended standards is to maintain provenance (geographic locality) records of plant origin by geo-referencing original plant sources and indexing this information (Falk et al 1996;Guerrant et al 2004;Vitt et al 2010;. Provenance records are critical when species are rare in the wild, because species purity is important to preserve in cultivation, and genotypic diversity could act as biological insurance against environmental fluctuations (Pavlik et al 1993;Gordon 1994;Bischoff et al 2010). This controlled propagation approach is especially important if reintroduction is deemed necessary to Box 3: Collaboration contributing to conservation.…”
Section: Commercial Propagation and Species Conservationmentioning
confidence: 99%
“…ex Greene, a federally-listed endangered borage native to California grasslands (Carlsen et al 2000). This reduction in fecundity has been found in other native species, both annual and perennial (Guerrant 1992;Gordon and Rice 1993;Pavlik et al 1993). In California, fire has been used to control exotic annual grasses and remove thatch to stimulate native forb populations and to also re-establish native perennial bunch grasses (George et al 1992;Menke 1992;Meyer and Schiffman 1999).…”
Section: Introductionmentioning
confidence: 99%